Association between population structure and allele frequencies of the glycogen synthase 1 mutation in the Austrian Noriker draft horse. (1st August 2016) - Druml, T.; Grilz‐Seger, G.; Neuditschko, M.; Brem, G.
Summary: The aim of this study was to determine the allele frequency of the glycogen synthase 1 ( GYS1 ) mutation associated with polysaccharide storage myopathy type 1 in the Austrian Noriker horse. Furthermore, we examined the influence of population substructures on the allele distribution. The study was based upon a comprehensive population sample (208 breeding stallions and 309 mares) and a complete cohort of unselected offspring from the year 2014 (1553 foals). The mean proportion of GYS1 carrier animals in the foal cohort was 33%, ranging from 15% to 50% according to population substructures based on coat colours. In 517 mature breeding horses the mutation carrier frequency reached 34%, ranging on a wider scale from 4% to 62% within genetic substructures. We could show that the occurrence of the mutated GYS1 allele is influenced by coat colour; genetic bottlenecks; and assortative, rotating and random mating strategies. Highest GYS1 carrier frequencies were observed in the chestnut sample comprising 50% in foals, 54% in mares and 62% in breeding stallions. The mean inbreeding of homozygous carrier animals reached 4.10%, whereas non‐carrier horses were characterized by an inbreeding coefficient of 3.48%. Lowest GYS1 carrier frequencies were observed in the leopard spotted Noriker subpopulation. Here the mean carrier frequency reached 15% in foals, 17% in mares and 4% in stallions and inbreeding decreased from 3.28% in homozygous non‐carrier horses to 2.70% in heterozygous horses and 0.94% in homozygous carriers. This study illustrates that lineage breeding and specified mating strategies result in genetic substructures, which affect the frequencies of the GYS1 gene mutation.